Fisheries and the law in Europe : regulation after Brexit - Fernández, Jonatan Echebarria; Johansson, Tafsir; Skinner, Jon A.; Lennan, Mitchell (Legal perspectives on Brexit, 2022)
"Fisheries and the Law in Europe Examining fisheries, Brexit, the Trade and Cooperation Agreement and its consequences for the Fishing Industry in the UK and the EU, this book explores key issues within the complex topic of fisheries after Brexit. Assessing the new fishing relationship between the UK and the EU which will continue to develop over the next decade, it provides an important and study of the state of fisheries post-Brexit. Taking a cross cutting economic, legal and policy approach, the book outlines the social and economic impacts of Brexit on the UK and EU fishing industries. It critically analyses the provisions relevant to fisheries in the TCA, reflects on the bilateral fishing negotiations between the EU, UK and Norway providing inferences as to what the "new and special relationship" might be in fisheries. It then focuses on the 2020 Fisheries Act and explores internal divergences in the nations of the UK because of devolution. Taking an international approach, it offers an exploration of cooperation in fisheries enforcement, international and regional obligations in marine conservation, and the new horizons for the UK in international fisheries organizations and arrangements now it is no longer a member of the EU. It offers an overview of expert opinion on fisheries post-Brexit, highlighting lessons learned and future developments for fisheries in a post-Brexit world. Having finally signed the Trade and Cooperation Agreement on 31 December 2020 after tense negotiations, the United Kingdom and European Union have found themselves in a new fisheries relationship. This book maps the complex social, economic, legal and policy issues of fisheries in a post-Brexit world and will be of interest to stakeholders and scholars. Jonatan Echebarria Fernández is Associate Professor of Law at the Department of Law and Governance, BI Norwegian Business School, Oslo, Norway. He is Honorary Lecturer at The City Law School (City, University of London, UK) and a Spanish qualified lawyer. He holds a PhD in Law from the Copenhagen Business School. Tafsir Matin Johansson holds a Ph.D. in Maritime Affairs and currently serves as an Associate Research Officer at the World Maritime University-Sasakawa Global Ocean Institute. Jon A. Skinner is a retired Commander, US Navy, and a long time Alaskan resident. His PhD from the University of Alaska Fairbanks is Interdisciplinary - Polar Geography and Strategic Studies. He currently serves as an Adjunct with at Matanuska-Susitna College, University of Alaska Anchorage, USA. Mitchell Lennan is an Affiliate Researcher at the Strathclyde Centre for Environmental Law & Governance (SCELG), University of Strathclyde, Glasgow, Scotland. At the time publication, Mitchell is completing his PhD at Strathclyde, examining the international legal challenges presented by shifting fish stocks due to climate change"--